Metafiction : the theory and practice of self-conscious fiction - Waugh, Patricia (New accents (Routledge (Firm)), 1993)
Metafication focuses on the state of contemporary fiction in Britain and America and explores the political, social and economic factors which have an effet on the critical judgement of fiction.